The Students’ Flow Experience With the Continuous Intention of Using Online English Platforms - Zhao, Hong; Khan, Asif (Frontiers in Psychology, 2022)
Built on the integrated theoretical framework of antecedents of flow and expectation confirmation model (ECM), this research investigates the way flow experience drives the online students’ intention to engage in online English teaching platforms. This study focused on the online students engaged in online English learning platforms in Taiwan. A total of 500 online students were selected. An online survey was conducted with the help of a marketing research agency located in Taiwan. According to the results, the online students' flow experience was found to be in a significant relationship with continuous intention. The antecedents including perceived enjoyment, challenge, and situational involvement were found to be in a positive relationship with flow experience, however confirmation and perceived vividness did not have significant effects on the flow. Furthermore, flow and confirmation were found to be in a significant relationship with perceived usefulness and satisfaction. Moreover, perceived usefulness was found to be in a significant relationship with satisfaction and continuous intention. Lastly, satisfaction was found to be in a significant relationship with continuous intention. Finally, the questions proposed in this research with their empirical findings offer profound understanding for establishing a well-devised online English learning platform that can motivate online learning. These results and managerial implications for online English language platforms are innovative and significant in practice.